2016
DOI: 10.1002/slct.201600273
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Emission Intensities of Binary Films Composed of Fluorescent Amorphous Molecular Materials and p‐Toluenesulfonic Acid in Response to Exhaled Breath

Abstract: We have found that fluorescence emission of binary films composed of fluorescent amorphous molecular materials, 4-[bis(4methylphenylaryl)amino]benzaldehyde (BMABA) and 4-[bis(4methylphenylaryl)amino]acetophenone (BMAAP), with p-toluenesulfonic acid (TsOH) was quenched at ambient dry atmosphere but enhanced when we breathed onto their films. When pausing the breath, the emission was again quenched. Moisture in the exhaled breath was suggested to play a role for such phenomena. It was suggested that some BMABA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In addition to these single films, amorphous molecular materials can be form homogeneous and/or phase‐separated films with other materials. We have recently been performing studies of such binary systems with smart functions [5–7] . Among them, we have reported that the binary films of aminoazobenzene‐based amorphous molecular materials with organic acids exhibited drastic and reversible color changes in response to moisture [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these single films, amorphous molecular materials can be form homogeneous and/or phase‐separated films with other materials. We have recently been performing studies of such binary systems with smart functions [5–7] . Among them, we have reported that the binary films of aminoazobenzene‐based amorphous molecular materials with organic acids exhibited drastic and reversible color changes in response to moisture [6] .…”
Section: Introductionmentioning
confidence: 99%
“…We have recently been performing studies of such binary systems with smart functions. [5][6][7] Among them, we have reported that the binary films of aminoazobenzene-based amorphous molecular materials with organic acids exhibited drastic and reversible color changes in response to moisture. [6] It was suggested that the phenomena were due to protonation to the aminoazobenzene caused by the organic acid and deprotonation affected by moisture and that the acidity levels and concentrations of the organic acids were important factors affecting the color of the film and its response to moisture.…”
Section: Introductionmentioning
confidence: 99%
“…These materials were also found to exhibit aggregation induced emission enhancement [13,14]. In addition, mixed amorphous films of these materials with p-toluene sulfonic acid exhibited emission modulations in response to exhaled breath, i.e., moisture around their films [15].…”
Section: Introductionmentioning
confidence: 96%
“…For example, we have reported that spincoated films of diarylaminobenzaldehyde-based emitting amorphous molecular materials exhibited vapochromic emission [11]. In addition to such materials with single component systems, we have recently been studying the creation of hybrid systems of amorphous molecular materials with other materials exhibiting smart functions [13][14][15][16][17][18][19][20][21][22][23]. We have reported that the hybrid films of aminoazobenzene-based amorphous molecular materials with organic acids exhibited drastic and reversible color changes in response to moisture [20].…”
Section: Introductionmentioning
confidence: 99%
“…Novel moisture-sensitive hybrid films composed of diarylaminobenzaldehyde-based emitting amorphous molecular materials with ptoluenesulfonic acid were found to exhibit OFF-ON switching of fluorescent in response to moisture [22]. Very recently, we have investigated the response of emission properties to moisture for hybrid films composed of 4-[bis(4-methylphenyl)amino]benzylideneaniline (BMBZA) with a variety of organic acids, and finally found that hybrid films of BMBZA with organic acids with appropriate acidities, benzoic acid (BA) and pentafluorobenzoic acid (PFBA), exhibited the emission color changes in response to moisture [23].…”
Section: Introductionmentioning
confidence: 99%